Perancangan model kemasan distribusi minuman kopi cup menggunakan kansei engineering (studi kasus kopi ruang normal) - Novi Purnama Sari; Iffat Halimatus Sa’diyah; Muryeti Muryeti (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Ruang Normal Coffee UMKM implements online buying and selling in marketing their products, but these UMKM do not yet have distribution packaging to protect the product during delivery. Based on the field survey, the distribution problems were the coffee cup packaging being dented, leaking, difficult to carry, and unattractive. The distribution packaging is currently considered not following consumer preferences because it is only in the form of clear plastic. This study aims to design packaging for distributing MSME coffee drinks in the Normal Room according to consumer preferences. The method used is Kansei Engineering (KE). KE implementation is supported by decision-making methods in determining packaging design concepts and packaging design elements. The term frequency-inverse document frequency (TFIDF) and principal component analysis (PCA) methods determine the design concept. In contrast, the Rough Set method determines the design elements. Sampling of respondents using purposive sampling with a minimum number of 30 respondents. The results of this study were that there were 21-word pairs based on TFIDF extraction and 40 packaging samples. The design concept was obtained through PCA analysis of the two main components that have a variance value of 1, namely PC-1 produces the concept of